Síntese de 1,3-imidazois-2,4,5-trissubstituídos derivados de calcogenofenos - Rodrigues, Mariele Borkowski (2014)
In the following work, a series of new 2,4,5 trisubstituted 1,3-imidazoles 11 and 12 were synthesized from 1-aryl-2-(chalcogenophen-2-yl)-1,2-diketones targeting the union of two classes of interesting heterocycles the imidazoles and chalcogenophenes. Using a modified Radziszewski multicomponent reaction for the synthesis of 2,4,5-trisubstituded 1,3-imidazoles 11 and 12, is reacted 1-aryl-2-(chalcogenophen-2-yl)-1,2-diketones 8a-c and 9a-c with aldehydes 10a-d (a = benzaldehyde, b = 4-methoxy-benzaldehyde, c = 4-chloro-benzaldehyde and d = octanal) in ammonium acetate and acetic acid. Compounds 11, thiophene derivatives, and compounds 12, selenophene derivatives were obtained with yields ranging 44-98% and from 37-82%, respectively. The study can demonstrate both the reactivity of 1,2-diketones used as the substituents exert influence in the formation of 2,4,5-trisubstituded 1,3-imidazoles.